Legal Analysis of the Authority of the Demak Regency General Election Supervisory Body in Supervising and Handling Criminal Offenses in the 2024 General Election - Marstyasih, Kusfitria; Ma'ruf, Umar (Jurnal Hukum Khaira Ummah, 2025)
Bawaslu has the authority to handle election violations which previously only had the nature of supervision and study. Bawaslu has the authority to examine, review and decide on cases related to election violations committed by election participants and organizers. The purpose of this research is to find out and analyze the authority of the General Election Supervisory Body in supervising and handling General Election Crimes in Demak Regency as well as to find out and analyze the obstacles and solutions for the General Election Supervisory Body in supervising and handling General Election Crimes in 2024 in Demak Regency. the obstacles and solutions for the General Election Supervisory Body in supervising and handling General Election Crimes in 2024. This legal research uses empirical legal research methods. Empirical juridical research, namely legal research using legal principles and principles in reviewing, viewing and analyzing problems in research, in addition to reviewing the implementation of law in practice. The theories used in this research are the theory of authority and the theory of legal effectiveness. Based on the research results, it can be concluded: 1) The authority of the General Election Supervisory Agency in supervising and handling General Election Crimes in Demak Regency, in this case, Bawaslu's authority in supervising and handling election crimes is a form of attribution of authority granted directly by Law Number 7 of 2017, which confirms the legality and legitimacy of Bawaslu's actions as part of the legal and constitutional function of election supervision. Bawaslu has a crucial role in ensuring that the 2024 Election in Demak Regency runs honestly and fairly through monitoring, preventing and taking action against various election violations, including the involvement of ASN and election crimes through the Integrated Law Enforcement Center (Gakkumdu). 2) Obstacles and solutions for the General Election Supervisory Agency in carrying out supervision and handling criminal acts in the 2024 General Election, various challenges such as limited human resources and budget, difficulty detecting the practice of money politics and black campaigns, as well as a lack of public understanding regarding the task of election supervision. To overcome these obstacles, Bawaslu needs to strengthen the capacity of supervisors through training and recruitment, utilize technology in monitoring, and improve coordination with civil society, media and law enforcement agencies to create cleaner, more transparent and more democratic elections.